COMPARISON OF OUTCOME OF AMINOPHYLLINE AND CAFFEINE CITRATE IN PREVENTION OF APNEA OF PREMATURITY (The Research of Medical Science Review, 2025)
Background: Apnea of prematurity (AOP) is a common condition in preterm neonates due to immature respiratory control. Methylxanthines such as caffeine and aminophylline are frequently used as respiratory stimulants in clinical practice. Objective: To compare the efficacy and complications of caffeine versus aminophylline in the treatment of AOP in premature neonates at a tertiary care hospital. Methodology: This randomized controlled trial was conducted at the Department of Pediatrics, Fauji Foundation Hospital, Rawalpindi. A total of 674 neonates diagnosed with AOP were enrolled and randomly divided into two equal groups (n=337 each). Group A received caffeine citrate, and Group B received aminophylline. Efficacy was assessed based on the recurrence of apnea, while complications including patent ductus arteriosus (PDA) and necrotizing enterocolitis (NEC) were monitored. Results: The study showed that caffeine significantly reduced the recurrence of apnea in preterm neonates compared to aminophylline (8.9% vs. 19.3%; p = 0.001). Additionally, caffeine was associated with a lower incidence of complications, including PDA (5.3% vs. 13.9%; p = 0.002) and NEC (0% vs. 2.3%; p = 0.004). These results suggest that caffeine is more effective and safer for treating AOP in premature neonates. Conclusion: Caffeine was more effective than aminophylline in reducing recurrent AOP episodes and was associated with fewer complications. Caffeine should be preferred for AOP management in premature neonates.